(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
In this article, East people’s history ,culture, language of the great specialist Y.E.Bertels life and work ,essence of his scientific activity are revealed.At the same time, the article talks about the contribution of the great thinker Jami’s scientific heritage of learning